Migration Challenge for PAYG - Gurgen Aslanyan (FIW - Research Centre International Economics, 2012)
Immigration has been popularised in the economics literature as a tool to balance the troubled PAYG pension systems. A pivotal research by Razin and Sadka showed that unskilled immigration can surmount the pension problem and, further, boost the general welfare in the host economy. However a large strand of current economics literature is engaged in identifying mechanisms through which unskilled immigration, while solving the pension problem, causes undesired shifts in general welfare. This work shows that actually recurring unskilled immigration may challenge the entire pension system and decrease the pension benefits themselves.
Keywords: J18; F22; H55; E61; 330; Public Pensions; PAYG; Unskilled Migration